Measurement of the Orbital Soft Tissue Volume in Chinese Adults Based on Three-Dimensional CT Reconstruction - Yi Du; Bing-Yao Lu; Jun Chen; Jian-Feng He (Journal of Ophthalmology)
Quantitative measurement of the orbital soft tissue volume plays a very important role in the study of orbital diseases. The purpose of this study is to establish a computed tomography- (CT-) based three-dimensional (3D) reconstruction model and measure the orbital soft tissue volume in Chinese adults. We collected data from 103 Chinese adults (52 males and 51 females) who underwent orbital CT. The CT images of these adults were used to reconstruct a 3D model of the orbital bony cavity, orbital fat, extraocular muscle, and intraorbital optic nerve using Mimics software, and their respective volumes were measured. The mean (±SD) orbital bony cavity volume (OV), orbital fat volume (FV), extraocular muscle volume (MV), and intraorbital optic nerve volume (iONV) of the males were 22.2 ± 2.2 cm3, 8.9 ± 1.8 cm3, 1.9 ± 0.34 cm3, and 0.41 ± 0.08 cm3, respectively. The mean OV, FV, MV, and iONV of the females were 20.2 ± 1.5 cm3, 8.1 ± 1.7 cm3, 1.6 ± 0.3 cm3, and 0.36 ± 0.074 cm3, respectively, which were all significantly lower than those in males (all p<0.05). FV (r = 0.370; p<0.001) and MV (r = 0.283; p=0.007) were significantly correlated with body mass index (BMI), while iONV was not correlated with BMI (r = −0.070; p=0.480). This study shows that FV, MV, and iONV were higher in males than in females. With increasing BMI, FV and MV both increased, but iONV did not exhibit this trend.